تقدير ثابت هلدر للتحويل المحافظ الذي ينقل القرص الواحدي إلى مضلع محدب ذو n ضلع (Latakia University Journal -Basic Sciences Series, 2018)
في هذا العمل نقوم بتقدير ثابت هلدر للتحويل المحافظ الذي ينقل القرص الواحدي K إلى المضلع المحدب المغلق  G الذي يملك n  ضلع , توجد دراسة تثبت وجود هذا الثابت و تبين أن أس هلدر لهذا التحويل يعطى بالعدد  حيث:  الزوايا الداخلية للمضلع.   In this study, we estimate Holder's constant of conformable mapping which maps  unitary disc into a convex  polygon of  n  sides. There are some studies that prove the existence of this constant and explain the relationship between the Polygon angles  and  Holder's index     :.